A Plasma Long‐Chain Acylcarnitine Predicts Cardiovascular Mortality in Incident Dialysis Patients. Issue 6 (5th December 2013) - Kalim, Sahir; Clish, Clary B.; Wenger, Julia; Elmariah, Sammy; Yeh, Robert W.; Deferio, Joseph J.; Pierce, Kerry; Deik, Amy; Gerszten, Robert E.; Thadhani, Ravi; Rhee, Eugene P.
Abstract : Background: The marked excess in cardiovascular mortality that results from uremia remains poorly understood. Methods and Results: In 2 independent, nested case‐control studies, we applied liquid chromatography‐mass spectrometry‐based metabolite profiling to plasma obtained from participants of a large cohort of incident hemodialysis patients. First, 100 individuals who died of a cardiovascular cause within 1 year of initiating hemodialysis (cases) were randomly selected along with 100 individuals who survived for at least 1 year (controls), matched for age, sex, and race. Four highly intercorrelated long‐chain acylcarnitines achieved the significance threshold adjusted for multiple testing ( P <0.0003). Oleoylcarnitine, the long‐chain acylcarnitine with the strongest association with cardiovascular mortality in unadjusted analysis, remained associated with 1‐year cardiovascular death after multivariable adjustment (odds ratio per SD 2.3 [95% confidence interval, 1.4 to 3.8]; P =0.001). The association between oleoylcarnitine and 1‐year cardiovascular death was then replicated in an independent sample (n=300, odds ratio per SD 1.4 [95% confidence interval, 1.1 to 1.9]; P =0.008). Addition of oleoylcarnitine to clinical variables improved cardiovascular risk prediction using net reclassification (NRI, 0.38 [95% confidence interval, 0.20 to 0.56]; P <0.0001). In physiologic profiling studies, we demonstrate that the fold change in plasma acylcarnitine levels from the aorta to renal vein and from pre‐ to post hemodialysis samples exclude renal or dialytic clearance of long‐chain acylcarnitines as confounders in our analysis. Conclusions: Our data highlight clinically meaningful alterations in acylcarnitine homeostasis at the time of dialysis initiation, which may represent an early marker, effector, or both of uremic cardiovascular risk.